Spin‐coating fabrication of high‐yield and uniform organic thin‐film transistors via a primer template growth - Zhenxin Yang; Jiale Su; Junzhan Wang; Xuanhe Li; Fushun Li; Juntao Hu; Nan Chen; Zhang Tao; Delong Yang; Deng‐Ke Wang; Qiang Zhu; Yuhui Liao; et al. (Aggregate)
Abstract Solution coating of organic semiconductors offers great potential for achieving low‐cost and high‐throughput manufacturing of large‐area and flexible electronics. However, the solution processability of semiconducting small molecules for fabricating uniform and reliable thin‐film devices poses challenges due to the low viscosities of small‐molecule solutions. Here, we report a universal approach employing a primer template (PT) to enhance the spreadability of small‐molecule solutions on silicon wafers, enabling the spin‐coating fabrication of uniform thin films composed of millimeter‐scale grains with complete large‐area coverage and well‐ordered molecular packing. Using PT, we fabricated organic thin‐film transistors (OTFTs) using solutions containing various small molecules such as rubrene and 2‐decyl‐7‐phenyl‐[1]benzothieno[3,2‐b][1]benzothiophene. The device yield of all fabricated OTFTs is consistently 100% while achieving a high average mobility of 1.62 cm2 V−1 s−1 with a device‐to‐device variation of 7.7% measured in ambient air condition. In addition, the utilization of PT resulted in a batch‐to‐batch variation of 12.5% in device performance over dozens of OTFT devices. The key industrial manufacturing metrics, such as device yield, reproducibility, and performance uniformity of the PT OTFTs, are among the best for devices fabricated using solution spin‐coating techniques.